A study on the competitive strategy of the universal postal service provider - Dobrodolac, Momčilo; Lazarevic, Dragan; Švadlenka, Libor; Zivanovic, Milina (Taylor and Francis, 2016)
We analysed how the universal postal service providers could employ their specificities to achieve an advantage over the growing competition. The basic input for the model is expert opinions. We interviewed 18 experts in five stages. As a multiple criteria decision support method, we used an analytic hierarchy process. Further, we proposed a geometric method for determining the business area where a company should focus its biggest attention to achieve the best result. By implementing the proposed model, a company should obtain two types of business directions, the first related to the proposed activities and the second to the business areas. To demonstrate the applicability of the proposed methodology, we tested and verified it in the case of the Serbian universal postal service provider which is a state-owned company called the Post of Serbia.
Studie konkurenční strategie poskytovatele univerzální poštovní služby
Keywords: Universal postal service provider; competitive strategy; decision-making; geometric method; posyktovatel univerzální poštovní služby; konkurenční strategie; rozhodovací proces; geometrické metody